The Role of Psychiatrists in Providing Information to Investigators - Heriyanto; Ichsan, Nursyamsi; Hasmiati Attas, Nasrah (Journal of Indonesian Scholars for Social Research, 2022)
The intersection of law and psychiatry is explored, emphasizing the necessity of expert opinions in substantiating claims of psychological harm and its legal ramifications. With the advancement of legal and medical sciences, there's an increasing reliance on psychiatric evaluations to provide a comprehensive understanding of a defendant's mental state, the effects of psychological violence, and the potential for resulting mental disorders. Moreover, the paper outlines the procedural aspects of incorporating psychiatric insights into legal evidence, from the initial stages of investigation to the final adjudication in court. It underscores the importance of Visum et Repertum (VeR) reports in establishing the facts of a case, especially in the context of psychological injuries, where physical evidence may be minimal or absent. Through a detailed discussion of the legal framework surrounding expert testimony and the presentation of psychiatric findings, the study advocates for a more informed and nuanced approach to handling cases involving mental health issues. The synthesis of legal principles and psychiatric expertise not only aids in achieving justice but also ensures a more empathetic and informed legal process. By acknowledging the profound impact of psychological violence and the critical insights provided by psychiatry, the paper calls for enhanced collaboration between the legal system and mental health professionals.